Her2-Positive and Microsatellite Instability Status in Gastric Cancer—Clinicopathological Implications - Bermúdez, Ana; Arranz-Salas, Isabel María; Mercado-Sáenz, Silvia; López-Villodres, Juan Antonio; González, Virginia; Ríus-Díaz, Francisca; Ortega-Jiménez, María Victoria; Alba-Linero, Carmen; Hierro-Martín, María Isabel; Bermúdez-Flores, Diego Teófilo (MDPI, 2021)
Gastric cancer (GC) is one of the leading causes of cancer-related death. The combination of new molecular classifications with clinicopathological data could contribute to the individualization of patients and to the development of new therapeutic strategies. We examined the various associations in two molecular types of GC: HER2-positive (human epidermal growth factor receptor 2) and microsatellite instability (MSI), assessing their influence on treatment and prognosis. A retrospective study of 142 GC patients was performed with molecular characterization through HER2 overexpression and DNA repair protein expression for MSI. The percentage of HER2-positive tumors was 13.4%, predominantly in men. Correlations were found with intestinal type, metastases, advanced stages and chemotherapy. Almost 75% of HER2-positive patients died. MSI occurred in 16.2%, associated with advanced age, female sex, distal location and intestinal type. These patients had few metastases and low stages. The percentage of deaths was higher among MSI patients who received perioperative chemotherapy. The determination of HER2 and MSI status in GC is important for their association with specific clinicopathological features and for their prognostic and predictive value.
Institutional Review Board Statement: The study was conducted according to the Declaration of Helsinki, national and international guidelines and approved by the Provincial Research Ethics Committee of Malaga, Spain (approval 21 February 2019, number TFG-NCCG-2019). Informed Consent Statement: All the subjects provided written informed consent before participating in the study. Written informed consent for publication obtained from participating patients who can be identified. Data Availability Statement: The data that support the findings of this study are available from the corresponding author upon reasonable request. Acknowledgments: The authors would like to thank Maria Repice for her help with the English version of the text.
Keywords: Estómago - Cáncer; gastric cancer; molecular classification; HER2; microsatellite instability; clinicopathological features